2012
DOI: 10.1590/s0034-70942012000500009
|View full text |Cite
|
Sign up to set email alerts
|

Influência da posição do dreno pleural na função pulmonar de pacientes submetidos à revascularização do miocárdio

Abstract: Summary: Ozelami Vieira IBC, Vieira FF, Abrão J, Gastaldi AC -Influence of Pleural Drain Insertion in Lung Function of Patients Undergoing Coronary Artery Bypass Grafting. Background and objectives:Longitudinal, prospective, randomized, blinded Trial to assess the influence of pleural drain (non-toxic PVC) site of insertion on lung function and postoperative pain of patients undergoing coronary artery bypass grafting in the first three days post-surgery and immediately after chest tube removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…2 A dor no pós-operatório somada à necessidade do uso de dreno podem contribuir para o aumento no tempo de internação hospitalar, pois ocasionam a imobilização torácica e a respiração superficial, acarretando diminuição do volume corrente. [2][3] Além da localização do dreno, a extubação precoce e a retirada do dreno em até 24 horas reduzem a dor no pós-operatório imediato, assim como o tempo de internação na unidade de terapia intensiva (UTI). [2][3] Um estudo 4 que avaliou a gravidade dos pacientes em pós-operatório de cirurgia cardíaca (revascularização do miocárdio e cirurgia valvares), por meio do Therapeutic Intervention Scoring System (TISS) 28, evidenciou que são pacientes graves e hemodinamicamente instáveis.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…2 A dor no pós-operatório somada à necessidade do uso de dreno podem contribuir para o aumento no tempo de internação hospitalar, pois ocasionam a imobilização torácica e a respiração superficial, acarretando diminuição do volume corrente. [2][3] Além da localização do dreno, a extubação precoce e a retirada do dreno em até 24 horas reduzem a dor no pós-operatório imediato, assim como o tempo de internação na unidade de terapia intensiva (UTI). [2][3] Um estudo 4 que avaliou a gravidade dos pacientes em pós-operatório de cirurgia cardíaca (revascularização do miocárdio e cirurgia valvares), por meio do Therapeutic Intervention Scoring System (TISS) 28, evidenciou que são pacientes graves e hemodinamicamente instáveis.…”
Section: Introductionunclassified
“…[2][3] Além da localização do dreno, a extubação precoce e a retirada do dreno em até 24 horas reduzem a dor no pós-operatório imediato, assim como o tempo de internação na unidade de terapia intensiva (UTI). [2][3] Um estudo 4 que avaliou a gravidade dos pacientes em pós-operatório de cirurgia cardíaca (revascularização do miocárdio e cirurgia valvares), por meio do Therapeutic Intervention Scoring System (TISS) 28, evidenciou que são pacientes graves e hemodinamicamente instáveis. Também mostrou que a pontuação do escore aumentada no 3º e 4º dia de pós-operatório, associa-se com maior incidência de complicações e maior tempo de internação.…”
Section: Introductionunclassified
“…A recent study concluded that the positioning of the drains can reduce the forced vital capacity (FVC) and the expiratory volume in the first second (FEV1) also in patients undergoing CABG. 16 Although PEF was not part of the research by Vieira et al, They believed that this variable would also suffer negative changes based on the decrease in FVC. In addition to the presence of drains, the authors associated pulmonary dysfunction with chest wall edema and changes of the surfactant.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the presence of drains, the authors associated pulmonary dysfunction with chest wall edema and changes of the surfactant. 16 …”
Section: Discussionmentioning
confidence: 99%